HOW TO COMBINE THE SERBIAN STOCK INDEX WITH PRECIOUS METALS IN A MULTIVARIATE MARKOWITZ PORTFOLIO? - Živkov, Dejan; Mihajlović, Emilija; Lalošević, Miloš (International Journal of Economic Practice and Policy, 2024)
This paper tries to determine how to combine Serbian stock index, BELEXline, with four precious metals – gold, silver, platinum and palladium, in order to minimize risk. In the process of portfolio construction, we use theoretical concept of Markowitz. In particular, we first determine portfolio of five assets, then exclude an asset with the lowest share and repeat procedure till we reach a portfolio of two assets. In this way, we construct four portfolios of five, four, three and two assets. In five-asset portfolio, portfolio optimization process determines zero share of silver, because silver bears the highest risk of all other portfolio instruments. This, also, means that five- and four-asset portfolios have the same characteristics. On the other hand, in three-asset portfolio, that contain the Serbian index, gold and platinum, we find higher share of platinum, comparing to five-asset portfolio, because platinum has higher negative correlation with BELEXline, vis-à-vis gold-BELEXline pair. Two-asset portfolio, which includes only the index and gold, has higher risk in amount of 5% and 4%, in relation to four- and three-asset counterparts. General conclusion is that three-asset portfolio is the best one, since it has slightly higher risk than five or four-asset portfolio, but it has lower transaction cost, because it includes only three instruments.